Urban fire risk: Evaluation and emergency planning - Tiago Miguel Ferreira (2016)
The management, prevention and mitigation of urban risks are assumed as priority actions within the framework of any rehabilitation and requalification process at the urban scale, particularly in the case of the rehabilitation and refurbishment of old city centres. In the most specific domain of urban safety, seismic and fire risk, which can cause serious consequences, are part of the collective memory of several communities and must be inevitably highlighted. The severity of the resulting damages is a more than valid reason to strongly value prevention, planning and mitigation strategies, limiting their consequences and guaranteeing permanent improvement actions. In the view of the abovementioned, and in the scope of a research project carried out, a new urban fire risk assessment methodology was developed and applied to the old city centre of Seixal. This simplified methodology is based on a preestablished method designated ARICA. Over 500 buildings were assessed using this methodology, and the results were spatially analysed using an integrated geographical information system tool (GIS). It is worth noting that the integration of the risk results into a GIS platform is a valuable step towards the risk mitigation at a urban scale, allowing city councils or regional authorities to plan interventions on the basis of a global spatial view of the site under analysis leading to more accurate and comprehensive risk mitigation strategies that support the requirements of safety and emergency planning in case of urban fire.